Collaborative Dynamics in Electroacoustic Music Creativity: Telematic Dialogues Across Apparatuses - Chagas, Paulo C.; Lozo, Ivana Petković (Anais do Simpósio Brasileiro de Computação Musical; 2025: Anais do XIX Simpósio Brasileiro de Computação MusicalDO - 10.5753/sbcm.2025.12369, 2025)
This paper investigates the dynamics of electroacoustic music collaboration within complex technological, social, and philosophical frameworks. Emphasizing the interplay between human creativity and technical apparatuses, it draws on theoretical concepts such as Vilém Flusser’s telematic dialogue, Jacques Attali’s notion of composition as resistance, Martin Heidegger’s ontology of art and technology, and Niklas Luhmann’s systems theory. Through historical examples—including the WDR Electronic Music Studio—and recent works by composer Paulo C. Chagas and flutist Cássia Carrascoza, particularly Sound Imaginations: Telematic Immersion, the paper examines how electroacoustic practices generate new forms of authorship, co-presence, and symbolic ritual. These practices challenge conventional boundaries between composer, performer, audience, and machine, proposing instead a participatory model of creative exchange. Ultimately, the study argues that electroacoustic collaboration reshapes not only the process of music-making but also broader modes of technological engagement, cultural production, and social interaction in the digital era.